2018
DOI: 10.1186/s12977-018-0441-2
|View full text |Cite
|
Sign up to set email alerts
|

Promoter expression of HERV-K (HML-2) provirus-derived sequences is related to LTR sequence variation and polymorphic transcription factor binding sites

Abstract: BackgroundIncreased transcription of the human endogenous retrovirus group HERV-K (HML-2) is often seen during disease. Although the mechanism of its tissue-specific activation is unclear, research shows that LTR CpG hypomethylation alone is not sufficient to induce its promoter activity and that the transcriptional milieu of a malignant cell contributes, at least partly, to differential HML-2 expression.ResultsWe analyzed the relationship between LTR sequence variation and promoter expression patterns in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 66 publications
(106 reference statements)
2
42
0
Order By: Relevance
“…Previously published reports demonstrate that transcription for both 3q12.3 and 4p16.1b is initiated in their respective 5′ LTRs, while the transcription for 22q11.23 is through a separate LTR, located a little over 500 bp upstream of the provirus [53]. Notably, it has been reported that the 5′ LTR from the provirus 3q12.3 has evolved to include a duplication of the HOX-PBX transcription binding site as well as a SNP in the RFX3 transcription factor binding site [54]. This may explain why this provirus is highly transcribed in many different cell types and why it no longer is able to function as a RcRE.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published reports demonstrate that transcription for both 3q12.3 and 4p16.1b is initiated in their respective 5′ LTRs, while the transcription for 22q11.23 is through a separate LTR, located a little over 500 bp upstream of the provirus [53]. Notably, it has been reported that the 5′ LTR from the provirus 3q12.3 has evolved to include a duplication of the HOX-PBX transcription binding site as well as a SNP in the RFX3 transcription factor binding site [54]. This may explain why this provirus is highly transcribed in many different cell types and why it no longer is able to function as a RcRE.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published reports demonstrate that transcription for both 3q12.3 and 4p16.1b is initiated in their respective 5' LTRs, while the transcription for 22q11.23 is through a separate LTR, located a little over 500bp upstream of the provirus (53). Notably, it has been reported that the 5' LTR from the provirus 3q12.3 has evolved to include a duplication of the HOX-PBX transcription binding site as well as a SNP in the RFX3 transcription factor binding site (54). This may explain why this provirus is highly transcribed in many different cell types and why it no longer is able to function as a RcRE.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro model of human mammary epithelial cell transformation indicated the 5 LTR promoter activity is active in tumorigenic cells only, suggesting that the cellular environment of a cancer cell is a critical component for induction of LTR promoter activity (Montesion et al, 2017). LTR sequence variations, causing transcription factor binding site polymorphisms, are positively correlated with promoter expression patterns in human breast cancer cell lines (Montesion et al, 2018; Figure 2G). The presence of interferon-stimulated response elements (ISREs) in the promoter region of HERV-K suggests its expression could be regulated by inflammatory cytokines, which could explain its implication in autoimmune disorders (Manghera et al, 2016; Figure 2H).…”
Section: Long Terminal Repeats (Ltrs)mentioning
confidence: 99%